2017
DOI: 10.3389/fimmu.2017.01471
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation Increases the Sensitivity of Mouse Treg for TNFR2 Costimulation

Abstract: TNF receptor type 2 (TNFR2) has gained attention as a costimulatory receptor for T cells and as critical factor for the development of regulatory T cells (Treg) and myeloid suppressor cells. Using the TNFR2-specific agonist TNCscTNF80, direct effects of TNFR2 activation on myeloid cells and T cells were investigated in mice. In vitro, TNCscTNF80 induced T cell proliferation in a costimulatory fashion, and also supported in vitro expansion of Treg cells. In addition, activation of TNFR2 retarded differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…In contrast, we did not observe TNFRII-dependent changes in IL-2 signaling pathways (i.e., pSTAT-5, p70SK6, and pERK-1/2 levels). This is consistent with recent reports showing that TNFRII activation does not affect pSTAT-5 levels (17,45). Further studies are needed to clarify the molecular effects of TNFRII on CD4+ and CD8+ Treg cells.…”
Section: Cd4+foxp3+supporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, we did not observe TNFRII-dependent changes in IL-2 signaling pathways (i.e., pSTAT-5, p70SK6, and pERK-1/2 levels). This is consistent with recent reports showing that TNFRII activation does not affect pSTAT-5 levels (17,45). Further studies are needed to clarify the molecular effects of TNFRII on CD4+ and CD8+ Treg cells.…”
Section: Cd4+foxp3+supporting
confidence: 92%
“…Both M2‐polarized macrophages and Treg cells have been associated with arthritis recovery . While we cannot exclude a contribution of macrophages to the therapeutic effect of EHD2‐sc‐mTNF R2 , a recent study showed that TNFRII signaling in Treg cells induces secretion of IL‐10 , indicating a therapeutic role of Treg cells.…”
Section: Discussionmentioning
confidence: 84%
“…TNFR2 has been identified as a marker for activated Tregs. TNFR2 and its ligands can activate and stabilize Tregs in an inflammatory environment ( 92 94 ). A subset of Tregs with high TNFR2 expression exhibits maximally suppressive activities in both mouse and human, which makes them the most desirable cells for the treatment of autoimmune and inflammatory diseases ( 95 , 96 ).…”
Section: Tnf In Autoimmune and Inflammatory Diseasesmentioning
confidence: 99%
“…costimulation [355]. Efficient TNFR2 activation requires oligomerization of TNFR2 by membrane-bound TNF.…”
Section: Selective Tnfr2 Targetingmentioning
confidence: 99%